CoMMA : 32000 browsable manuscripts c. 800–1600, preserving original spelling and abbreviations.
https://www.inria.fr/en/comma-medieval-manuscripts-transcribed
Keywords: _open access

Medieval Soldier database (2009)
Our database contains the names of soldiers serving the English crown from the late 1350s to 1453. Most were fighting the French. In this second phase of the Hundred Years War major invasions of France were launched, including that of 1415 which culminated in Henry V’s victory at Agincourt 1415. We have also included soldiers serving in other theatres (Scotland, Ireland, Wales, Spain, Calais etc), and in all types of service (expeditions on land and sea, garrisons, escorts, standing forces). Why do we know so many names? The simple explanation is that soldiers received pay and this had to be audited. The financial officials of the crown were keen to check the soldiers were present and correct. The main way of doing this was by checking off their names at a muster, at the beginning of a campaign or during it, or every few months for troops in garrison. Thousands of muster rolls survive in archive collections in England, France and beyond. We also have the evidence of letters of protection which soldiers bought from the Chancery to prevent legal actions whilst they were absent from home.
Keywords: _open access

Digitised manuscripts and archives (British Library)
View more than 2,000 of our digitised manuscripts and archival documents, including the Sherborne Missal and Octateuch, Four Gospels and Synodicon.
Keywords: _open access

CoMMA, a Large-scale Corpus of Multilingual Medieval Archives (INRIA)
Browsable manuscripts c. 800–1600, preserving original spelling and abbreviations
Keywords: _open access

Medieval Libraries of Great Britain
Keywords: _open access

Projets Time Machine. Construire et diffuser ensemble des référentiels géohistoriques (Projets Time Machine)
Keywords: _open access

Royal Ontario Museum
Collections consacrées à l’art, à la nature et aux cultures du monde entier et de toutes les époques
Keywords: _open access

e-codices – Bibliothèque virtuelle des manuscrits en Suisse
Le but d′e-codices est de mettre à disposition tous les manuscrits médiévaux et une sélection de manuscrits modernes en Suisse dans une bibliothèque virtuelle. Pour l’instant, 2959 manuscrits de 100 collections différentes sont accessibles. La bibliothèque virtuelle sera progressivement enrichie.
Keywords: _open access

POP : la plateforme ouverte du patrimoine
Enluminures de manuscrits médiévaux d’une centaine de bibliothèques municipales françaises
Keywords: _open access

Mandragore. base iconographique pour les manuscrits de la BnF
Les collections de la Bibliothèque nationale de France abritent plusieurs dizaines de milliers de manuscrits dont le décor constitue l'un des plus riches musées de peinture au monde. La base Mandragore vous invite à l'explorer. Cette toute nouvelle version remplace le site de 2003, devenu obsolète. Retrouvez les 200 000 enluminures, dessins, sceaux, décors de reliures déjà décrits, avec des informations mieux structurées et de nouvelles fonctionnalités.
Keywords: _open access

ARCA BVMM- Bibliothèque virtuelle des manuscrits médiévaux
Bibliothèque numérique de l’IRHT, répertoire des cotes de manuscrits, incunables et livres anciens conservés dans les bibliothèques du monde entier.
Keywords: _open access

Digital Bodleian
Keywords: _open access

Grand corpus des littératures française et francophone, du Moyen âge au 20e siècle
Keywords: _UdeM only

Patrologia Latina
The Patrologia Latina Database is an electronic version of the first edition of Jacques-Paul Migne's Patrologia Latina, published between 1844 and 1855, and the four volumes of indexes published between 1862 and 1865. Patrologia Latina comprises the works of the Church Fathers from Tertullian in 200 AD to the death of Pope Innocent III in 1216. The complete Patrologia Latina is included with all prefatory material, original texts, critical apparatus and indexes. Migne's column numbers, essential references for scholars, are included.
Keywords: _UdeM only

Library of Latin Texts
Keywords: _UdeM only

ARTFL-FRANTEXT
ARTFL-FRANTEXT is the main ARTFL Database, comprising more than 3,600 French-language texts, 215 million words and 675,000 unique word forms. The corpus contains texts ranging from classic works of French literature to various kinds of non-fiction prose and technical writing. The eighteenth, nineteenth and twentieth centuries are about equally represented, with a smaller selection of seventeenth century texts as well as some medieval and Renaissance texts. Genres include novels, verse, theater, journalism, essays, correspondence, and treatises. Subjects include literary criticism, biology, history, economics, and philosophy. In most cases standard scholarly editions were used in converting the text into machine-readable form, and the data contain page references to these editions.

Arlima - Archives de littérature du Moyen Âge
Il se propose ainsi de fournir une couverture bibliographique aussi complète que possible sur un grand nombre d'auteurs et de textes du Moyen Âge, principalement de langues française et latine sans pour cela exclure les autres langues d'Europe occidentale.

Jonas : Répertoire des textes et manuscrits médiévaux en langue d’oc et d’oïl - Institut de Recherche et d'Histoire des Textes, Section romane (Institut de recherche et d'Histoire des Textes)
La base Jonas est un répertoire des textes littéraires français et occitans du Moyen Âge et de la première modernité, ainsi que des manuscrits et imprimés les conservant.

Digital Collections | Leiden University Libraries
More than 300 medieval manuscripts from the Bibliotheca Vossiana
Keywords: _open access

Écrits médiévaux circulant sur le marché privé : la base de données Guard
Le projet GUARD – acronyme de Guarantee Unpreserved Archives Remain Documented – est porté par Nicolas Ruffini-Ronzani (Université de Namur et Archives de l’État à Namur) et Sébastien de Valeriola (Université libre de Bruxelles). Il vise à récupérer les informations éphémères qui circulent en ligne et dans les catalogues de ventes aux enchères à propos de documents d'archives médiévaux, de les compiler, de les structurer, et de les archiver de façon pérenne dans une base de données ouverte et collaborative.

CHI-KNOW-PO · GitLab (GitLab, 2024)
On the articulation between the realms of poetry and knowledge in Medieval China. Édition de textes de la Chine antique et médiévale, fouille de textes en vue de mettre au jour de possibles phénomènes de reprises et de contamination.

Ming Qing Women's Poetry Collection (CALASYS - CALA Academic Resources & Repository System)
Keywords: _open access

Ming Qing women's writings
This digital archive is a collaborative project among the libraries, including the McGill Library, the Harvard-Yenching Library, and the Peking University Library. As of December 2022, the archive provides free online access to 426 collections of women's writings published during Ming (1368-1644), Qing (1644-1911), and the Republican (1911-1949) periods. Users can search and browse more than 70,000 scanned images of texts and illustrations by the 5,240 women poets and writers and the 2,475 male writers who contributed to women's writings as editors/compilers or as writers of prefaces, biographies, endorsement verse, and postscripts.
Keywords: _open access

Dunhuang Papers
Morphological Data on 1000 Manuscripts from the "Pelliot Chinois" Collection of the Bibliothèque Nationale de France
Keywords: _open access

Unlocking the Records of London’s Medieval Foreign Trade - vanessarockel (On History, 2024)
This blog post was written by Dr Stephen Gadd, Software Developer and GIS Consultant. The IHR’s Centre for the History of People, Place and Community has been carrying out some exploratory research on the potential of analysing London’s medieval customs accounts digitally. Detailed, or ‘particular’ customs accounts recorded immense detail about the goods and practices […]

BnF Archives et manuscrits
Keywords: _open access

Frontier life: borderlands, settlement & colonial encounters - Adam Matthew Publications
Keywords: _UdeM only

Recently Digitized Manuscripts from the BAV (Biblioteca Apostolica Vaticana) (Vatican Manuscript Tracking)
This is a project to track the work of the Biblioteca Apostolica Vaticana in digitizing their collection of over 80,000 manuscripts.
Keywords: _open access

British History Online
The core printed primary and secondary sources for the medieval and modern history of the British Isles
Keywords: _open access

Vatican Apostolic Library
Keywords: _open access

Persian Language Rare Materials (Library of Congress)
The Library of Congress is home to a noteworthy collection of rare Persian language manuscripts, lithographic books and early imprints, as well as printed books, housed in the African and Middle Eastern Division (AMED) and the Rare Book and Special Collections Division. Most of these Persian manuscripts and lithographic books were procured for the Library in the 1930s by Kirkor Minassian (1874-1944), a renowned dealer in fine Islamic and Near Eastern arts with establishments both in New York and Paris. The Minassian acquisitions included treasures from the entire Middle East with rare books and manuscripts in Arabic, Persian, Turkish and Armenian languages. Since the 1930s the Library has continued to purchase a small number of Persian language manuscripts and lithographs at auctions, and from antique manuscript and book sellers including Christies and Sotheby's. The Library has also benefited from the generosity of people who have donated rare Persian materials they inherited from their families over the generations and which have been present in the United States or Europe before World War II.
Keywords: _open access

The National Archives, UK
Official archive of the UK government, and for England and Wales.. Spanning 1000 years of history. Non-ministerial department.
Keywords: _open access

World Historical Gazetteer
Index of place records with coordinates, historical metadata, linked toponyms, and ecological classifications
Keywords: _open access

Monasterium
Keywords: _open access

Project Gutenberg (Project Gutenberg)
Project Gutenberg is a library of free eBooks.
Keywords: _open access

Gallica
Keywords: _open access